Sie sind auf Seite 1von 16

International Journal of Pure and Applied Mathematics

Volume 84 No. 4 2013, 435-450


ISSN: 1311-8080 (printed version); ISSN: 1314-3395 (on-line version)
url: http://www.ijpam.eu
doi: http://dx.doi.org/10.12732/ijpam.v84i4.13
P A
ijpam.eu
ON A METHOD FOR CONSTRUCTING SOLUTIONS OF
DIFFERENTIAL EQUATIONS OF FRACTIONAL
ORDER WITH A HADAMARD TYPE OPERATOR
Batirkhan Turmetov
1
, Kanat Shinaliyev
2
Department of Mathematics
International Kazakh-Turkish
University named after A. Yasawi
Turkestan, 161200, REPUBLIC OF KAZAKHSTAN
Abstract: In this paper we investigate a method for constructing solutions of
dierential equations of fractional order with Hadamard type derivative. The
basis of this method is the construction of systems concerning the operator
of fractional dierentiation with Hadamard type derivative. We dene new
classes of special functions generalizing the Mittag-Leer functions, and related
to the dierential equations of fractional order. Properties of these functions
and their applications to solutions of fractional order dierential equations are
established. Analytical solutions of dierential equations of fractional order are
found as a series. Moreover, we consider normed systems of non-homogeneous
dierential equations of fractional order.
AMS Subject Classication: 35J40, 35J05
Key Words: fractional derivative, Hadamard operator, normed system, op-
erator method
Introduction
Let 0 < a < b < , > 0. For a given the following expression is called an
Received: January 21, 2013
c 2013 Academic Publications, Ltd.
url: www.acadpubl.eu

Correspondence author
436 B. Turmetov, K. Shinaliyev
integration operator of order in the sense of Hadamard[1]:
I

a
(f)(t) =
1
()
t
_
a
_
ln
t

_
1
f()

d , t > a.
Furthermore, we put I
0
a
(f)(t) f(t).
Let = t
d
dt
,
k
= (
k1
), k = 1, 2, ....
Then for (m1, m], m = 1, 2, ... the following expressions are called dif-
ferentiation operators of in the sense of, respectively, Hadamard and Hadamard-
Caputo, see [1]:
H
D

a
[f](t) =
m
_
I
m
a
f
_
(t),
HC
D

a
[f](t) = I
m
a
(
m
f) (t)
Let 0 1, m1 < m, m = 1, 2, ....Then operator
D
,
a
(f)(t) = I
(m)

m
I
(1)(m)
(f)(t)
is called dierentiation operator of order and type (see [2, 3]). It is clear
that if = 0 then the operator D
,
a
coincides with
H
D

a
, and when = 1
with the operator
HC
D

a
. Note that properties and applications of the operator
D
,
a
when 0 < 1, 0 1 have been studied in [2].
In this paper we study a method for constructing solutions of dierential
equations of the following form:
_
D
,
a

_
n
y(t) = h(t). (1)
where R, n = 1, 2, .... This method was studied for the dierential equa-
tions of integer order in [4], and for the equations of fractional order with
Riemann-Liouville type operator in [5, 6]. The basis of this method is the
construction of normed systems for the operators D
,
a
and D
,
a
.
Consider denition of the normed systems [4]. Let L
1
and L
2
be linear
operators given in a linear space of functions X. An innitely system of functions
f
k
(x) X, k = 1, 2, ..., where any nite subsystem is linear independent, is
called f normed concerning (L
1
, L
2
) with base f
0
(x), if everywhere in this
domain the following equality holds:
L
1
f
0
(x) = f(x), L
1
f
k
(x) = L
2
f
k1
(x), k = 1, 2, ...
A particular case of this denition is the case when L
2
is an identity oper-
ator. In this case, instead of normalizability on the pair of operators (L
1
, L
2
)
ON A METHOD FOR CONSTRUCTING SOLUTIONS OF... 437
we will talk about normalizability on one operator L
1
. If f(x) = 0, then the
system f
k
(x) X, k = 1, 2, ... is called 0normed or just normed [4].
An important property of the normed system is the following: if {f
k
(x)}
is a system of functions fnormed concerning (L
1
, L
2
) in the domain such
that the series y(x) =

k=0
f
k
(x) converges, and admits termwise application of
operators L
1
and L
2
, then the function y(x) in the domain is a solution of
the equation:
(L
1
L
2
) y(x) = f(x).
It is easy to check that if {f
k
(x)} is a system of functions fnormed con-
cerning L
1
in the domain , and the following equalities hold:
L
1
L
2
f
k
= L
2
L
1
f
k
, k = 1, 2, ... .
Then the system of functions
_
L
k
2
f
k
(x)
_
is f normed concerning (L
1
, L
2
)
in the domain . Therefore, to use the basic property of the normed system
of functions during the construction of solutions of equation (L
1
L
2
) y(x) =
f(x) it is necessary to nd fnormed in system of functions concerning the
operator L
1
.
1. Construction of Normed System for Homogenous Equation
Let 0 1, m 1 < m, m = 1, 2, ..., = (1 )(m ). Introduce
the coecients:
C(, , s, 0) = 1, C(, , s, i) =
(i + s + 1)
(s + 1)
, i 1,
where s = 0, 1, ..., m 1. Let us consider some properties of the operators I

a
and D
,
a
.
Lemma 1. Let s = 0, 1, ..., m1, m 1, then

m
_
ln
t
a
_
s
= 0. (2)
Proof. It is obvious that
_
ln
t
a
_
0
= 0 and
_
ln
t
a
_
= 1 . Then for all s 1 :

_
ln
t
a
_
s
= s
_
ln
t
a
_
s1
.
438 B. Turmetov, K. Shinaliyev
Further, by induction it easy follows that

k
_
ln
t
a
_
s
= s (s 1) ... (s k + 1)
_
ln
t
a
_
sk
, s k, (3)
and

k
_
ln
t
a
_
s
= 0, if k > s.
Consequently, for all s = 0, 1, ..., m1 equality (2) holds. Lemma is proved.
Lemma 2. Let > 1 and f(t) =
_
ln
t
a
_

. Then
I

a
(f)(t) =
( + 1)
( + + 1)
_
ln
t
a
_+
. (4)
Proof. By denition of the operator I

a
we have
I

a
(f)(t) =
1
()
t
_
a
_
ln
t

_
1 _
ln

a
_

=
=
1
()
t
_
a
_
ln
t
a
ln

a
_
1 _
ln

a
_

d ln

a
=
=
1
()
1
_
0
(1 )
1

d
_
ln
t
a
_
+
=
( + 1)
( + + 1)
_
ln
t
a
_
+
.
Lemma is proved.
Lemma 3. Let > m1 and f(t) =
_
ln
t
a
_

. Then
D
,
a
(f)(t) =
( + 1)
( + 1 )
_
ln
t
a
_
. (5)
Proof. Let > m 1. Due to the equality (4) for the functions I

a
(f)(t)
we get
I

a
(f)(t) =
( + 1)
( + 1 + )
_
ln
t
a
_+
.
ON A METHOD FOR CONSTRUCTING SOLUTIONS OF... 439
Then by the equality (3) we have

m
I

a
(f)(t) =
( + 1)
( + 1 + )

m
_
ln
t
a
_
+
=
=
( + 1)
( + 1 + )
( + )...( + m + 1)
_
ln
t
a
_
+m
=
=
( + 1)
( + 1 + m)
_
ln
t
a
_
+m
.
Further,
I
(m)
a
_
ln
t
a
_
+m
=
( + + 1 m)
( + + 1 m + (m))
_
ln
t
a
_
+m+(m)
.
Since + (m) = m, then
D
,
a
(f)(t) = I
(m)
a

m
I

a
(f)(t) =
=
( + 1)
( + 1 + m)
( + 1 + m)
( + 1 )
_
ln
t
a
_

=
( + 1)
( + 1 )
_
ln
t
a
_

Lemma is proved.
Corollary 1. Let = k + s , k = 1, 2, ..., s = 0, 1, ..., m 1 and
f(t) =
_
ln
t
a
_

. Then
D
,
a
(f)(t) =
(k + s + 1)
((k 1) + s + 1)
_
ln
t
a
_
k+s
. (6)
Lemma 4. Suppose that f
i
(t) =
1
C(,,s,i)
_
ln
t
a
_
i+s
, i = 0, 1, ... Then
f
i
(t) for any s = 0, 1, ..., m1 forms 0-normed system of the functions concern-
ing the operator D
,
a
.
Proof. Let i 1. Then,using (6) and denition of the coecients C(, , s, i),
we get
D
,
a
f
i
(t) =
(i + s + 1)
((i 1) + s + 1)

(s + 1 )
(i + s + 1)
_
ln
t
a
_
i+s
=
=
(s + 1 )
((i 1) + s + 1)
_
ln
t
a
_
(i1)+s
=
440 B. Turmetov, K. Shinaliyev
=
1
C(, , s, i 1)
_
ln
t
a
_
(i1)+s
= f
i1
(t).
If i = 0, then, by the equality (4), we have:
I

a
_
ln
t
a
_s
=
(s + 1)
(s + 1 + )
_
ln
t
a
_s
.
Since

m
_
ln
t
a
_
s
= 0 , s = 0, 1, ..., m1,
then
D
,
a
_
ln
t
a
_
s
= 0.
Lemma is proved.
Consider the function:

p
,,s
(t) =

i=p

ip
_
i
p
_
t
i+s
C(, , s, i)
,
where
p = 0, 1, ...,
_
i
p
_
=
i!
p!(i p)!
.
Introduce the following spaces:
C
,ln
[a, b] =
_
y(t) :
_
ln
t
a
_

y(t) C[a, b]
_
,
and
C

[a, b] =
_
y(t) C
,ln
[a, b] : D
,
a
y(t) C
,ln
[a, b]
_
, > 0.
It is obvious that the spaces C
,ln
[a, b] and C

,ln
[a, b] are linear. The basic
properties of the functions
p
,,s
(, t) are presented in the following theorem:
Theorem 1. Let m 1 < m, 0 1, s = 0, 1, ..., m 1. Then

p
,,s
(, t) C

,ln
[a, b], and for all p = 0, 1, ..., forms 0-normed system con-
cerning operator D
,
a
i.e. the following equalities hold:
_
D
,
a

_

0
,,s
(, t) = 0, (7)
_
D
,
a

_

p
,,s
(, t) =
p1
,,s
(, t), p 1. (8)
ON A METHOD FOR CONSTRUCTING SOLUTIONS OF... 441
Proof. Let p = 0. Then the function
0
,,s
(, t) can be presented as a
form:

0
,,s
(, t) =
_
ln
t
a
_

i=0

i
C(, , s, i)
_
ln
t
a
_
i+s
=
_
ln
t
a
_

y
1
(t),
where
y
1
(t) =

i=0

i
C(, , s, i)
_
ln
t
a
_
i+s
. (9)
It is known that for a gamma function the following asymptotical estimate
holds:
(z + 1) =

2z
_
z
e
_
z
_
1 + O
_
1
z
__
, z .
Then it is easy to show that the series (9 converges for t [a, b], and the
function y
1
(t) C[a, b]. Consequently,
0
,,s
(, t) C

[a, b]. Using operator


D
,
a
to the function
0
,,s
(, t), and taking account that the system f
i
(t) =
1
C(,,s,i)
_
ln
t
a
_
i+s
forms 0-normed system concerning operator D
,
a
, we re-
ceive
D
,
a
_

0
,,s

(, t) =

i=1

i
C(, , s, i 1)
_
ln
t
a
_
(i1)+s
=
=

i=0

i+1
C(, , s, i)
_
ln
t
a
_
i+s
=
0
,,s
(, t).
Therefore, D
,
a
_

0
,,s
_
(, t) C

[a, b], and it satises equality (7). Now


let p 1. We use operator D
,
a
to the function
p
,,s
(, t), and similarly as in
the case p = 0, we get
D
,
a
_

p
,,s
_
(, t) =

i=p

ip
_
i
p
_
D
,
a
f
i
(t) =
=

i=p

ip
_
i
p
_
1
C(, , s, i)
_
ln
t
a
_
(i1)+s
.
Further, in the last expression by changing the summation index and using
the equality:
_
i + 1
p
_

_
i
p 1
_
=
_
i
p
_
and
_
p
p
_

_
p 1
p 1
_
= 0,
442 B. Turmetov, K. Shinaliyev
we obtain
D
,
a

p
,,s
(, t)
p1
,,s
(, t) =
=

i=p1

j(p1)
C(, s, j)
__
i + 1
p
_

_
i
p 1
__ _
ln
t
a
_
j+s
=
=

i=p1

j(p1)
C(, s, j)
_
i
p
__
ln
t
a
_
j+s
=
p
,,s
(, t)
It follows that
(D
,
a
)
p
,,s
(, t) =
p1
,,s
(, t), p 1.
It is obvious that
p
,,s
(, t) C[a, b] for all p = 1, ..., n1 ,and
0
,,s
(, t)
C

[a, b]. Hence D


,
a

p
,,s
(, t) C

[a, b]. Theorem is proved.


Corollary 2. Suppose that conditions of theorem 1 hold for all p =
0, 1, 2, ..., n 1 and s = 0, 1, ..., m 1. Then the functions
p
,,s
(, t) sat-
isfy equality (1) when h(t) = 0.
Let p = 0. Transform the function
0
,,s
(, t) to the following form:

0
,,s
(, t) = (s + 1)

i=0

i
(i + s + 1)
_
ln
t
a
_
i+s
=
= (s + 1)
_
ln
t
a
_
s
E
,s+1
_

_
ln
t
a
_

_
,
where
E
,
(z) =

i=0
z
i
(i + )
is a Mittag-Leer type function, see [1].
2. Construction of Normed System for Non-Homogenous Equation
Consider the function
h
0
(t) =
t
_
a
(ln
t

)
1
E
,
_

_
ln
t

_
h()

d. (10)
ON A METHOD FOR CONSTRUCTING SOLUTIONS OF... 443
In further we assume that h(t) belongs to a class of functions for which all
the transactions in question are valid. Let us show that
_
D
,
a

_
h
0
(t) = h(t). (11)
Consider the case when (0, 1] . In this case by denition of the operator
D
,
a
we have
D
,
a
h
0
(t) =
1
(
1
)

t
_
a
_
ln
t

1
1

a
[h]()
d

,
where
1
= (1 ).
Then
D
,
a
h
0
(t) =
1
(
1
)
t
d
dt
_
_
_
t
_
a
1

1
_
ln
t

1
d
d
I

a
[h]()d
_
_
_
=
=
1
(
1
)
t
d
dt
_
_
_
1

1
_
ln
t

1
I

a
[h]()

= t
= a
+
t
_
a
_
ln
t

_
1
I

a
[h]()d
_
_
_
=
=
1
(
1
)
t
d
dt
_
_
_

t
_
a
_
ln
t

1
1
1
()

_
a
_
ln

_
1
h
0
()
d

_
_
_
=
=
1
(
1
)()
t
d
dt
t
_
a
h
0
()
t
_

_
ln
t

1
1
_
ln

_
1
d

.
Let us study inner integral. We get
t
_

_
ln
t

ln

_
ln

_
1
d ln

=
=
1
_
0
(1 z)

1
1
z
1
dz
_
ln
t

_
+
1
1
=
(
1
)()
( +
1
)
_
ln
t

_
+
1
1
.
444 B. Turmetov, K. Shinaliyev
Further, by the presentation of the function h
0
() and taking account that
+
1
= 1 , we have
t
_
a
h
0
()
_
ln
t

_
+
1
1
d

=
=
t
_
a
_
ln
t


_
a
_
ln

_
1

i=0

i
(i + )
_
ln

_
i
h()

d
d

=
=

i=0

i
(i + )
t
_
a
h()
t
_

_
ln
t

_
ln

_
i+1
d

=
=

i=0

i
(i + )
t
_
a
h()
(1 )(i + )
(i + + 1 )
_
ln
t

_
i
d

Therefore,
D
,
a
h
0
(t) = t
d
dt
_
_
_
t
_
a
h()
_

i=0

i
(i + 1)
_
ln
t

_
i
_
d

_
_
_
=
= t
h(t)
t
+
t
_
a
h()
_

i=1

i
(i + 1)
i
_
ln
t

_
i1
_
d

=
= h(t) +
t
_
a
h()
_
_

j=0

j+1
(j + )
_
ln
t

_
j+1
_
_
d

=
= h(t) +
t
_
a
h()
_
ln
t

_
1
E
,
_

_
ln
t

_
d

d =h(t) + h
0
(t)
Consequently,
D
,
a
h
0
(t) = h(t) + h
0
(t)
or the same
(D
,
a
)h
0
(t) = h(t).
ON A METHOD FOR CONSTRUCTING SOLUTIONS OF... 445
In general, when (m1, m] we can present function D
,
a
h
0
(t) in the
following form:
D
,
a
h
0
(t) = I

1
a

m
I

a
(h
0
)(t) =
1
(
1
)
t
_
a
_
ln
t

1
1
g()
d

, (12)
where g() =
m1
I

a
[h
0
]().
Now we study the function g(). To do this, we transform the function
I

a
[h
0
](). By denition of the operator I

a
, we have
I

a
h
0
(t) =
1
()
t
_
a
_
ln
t

_
1
h
0
()
d

=
=
1
()
t
_
a
_
ln
t

_
1

_
a
_
ln

_
1
E
,
_

_
ln

_
h()

d
d

=
=

i=0

i
(i + )
1
()
t
_
a
_
ln
t

_
1

_
a
_
ln

_
i+1
h()

d
d

=
=

i=0

i
(i + )
1
()
t
_
a
h()
t
_

_
ln
t

_
1
_
ln

_
i+1
d

=
=
t
_
a
_

i=0

i
(i + + )
_
ln
t

_
i+1+
_
h()

d
Further, since

m1
_
ln
t

_
i+1+
= (i + 1 + ) ... (i + + (m1))
and
(i++) = (i + + 1) ... (i + + (m1)) (i++(m1)),
then
D
,
a
h
0
(t) =
1
(
1
)
t
d
dt
_
_
_
t
_
a
1

1
_
ln
t

1
d
d
g()d
_
_
_
=
446 B. Turmetov, K. Shinaliyev
=
1
(
1
)
t
d
dt
_
_
_
t
_
a
_
ln
t

1
g()d
_
_
_
.
Now it is obvious that lim

g() = 0. Then by (12) as in the case (0, 1)


we get
D
,
a
h
0
(t) =
1
(
1
)
t
d
dt
_
_
_
t
_
a
1

1
_
ln
t

1
d
d
g()d
_
_
_
=
=
1
(
1
)
t
d
dt
_
_
_
t
_
a
_
ln
t

1
g()d
_
_
_
Further,
t
_
a
_
ln
t

1
1
g()d =
=

i=0

i
(i + + (m1))
t
_
a
_
ln
t

1
1

_
a
_
ln

_
i++m
h()

d
d

=
=

i=0

i
(i + + (m1))
t
_
a
h()

t
_

_
ln
t

1
1
_
ln

_
i++m
d

d =
= (
1
)

i=0

i
(i + 1)
t
_
a
_
ln
t

_
i
h()

d =
= (
1
)
t
_
a
_

i=0

i
(i + 1)
_
ln
t

_
i
_
h()

d
Consequently,
D
,
a
h
0
(t) = t
d
dt
_
_
_
t
_
a
_

i=0

i
(i + 1)
_
ln
t

_
i
_
h()

d
_
_
_
=
= h(t) +
t
_
a
_

i=1

i
(i + 1)
i
_
ln
t

_
i1
_
h()

d =
ON A METHOD FOR CONSTRUCTING SOLUTIONS OF... 447
= h(t) +
t
_
a
_
_

j=0

j
(j + )
_
ln
t

_
j+1
_
_
h()

d = h(t) + h
0
(t).
So,
(D
,
a
)h
0
(t) = h(t).
Further, suppose p = 0, 1, ... D
,
a
and
E
p
,
(, t) =

i=p

ip
_
i
p
__
ln
t
a
_
i
.
It is obvious that
E
0
,
(, t) = E
,
(, t)
when p = 0.
Introduce the function:
h
p
(t) =
t
_
a
_
ln
t

_
1
E
p
,
_
,
_
ln
t

_
h()
d

.
Theorem 2. Let m1 < m, 0 1,s = 0, 1, ..., m1.
Then the functions h
p
(t), p = 0, 1, ... form h-normed system concerning
operator, i.e. the following equalities hold:
_
D
,
a

_
h
0
(t) = h(t), (13)
_
D
,
a

_
h
p
(t) = h
p1
(t), p 1. (14)
Proof. Since when p = 0 E
0
,
(, t) = E
,
(, t) then we have proved
equation (13) above. Let p 1. As in the casep = 0 we present function
D
,
a
h
p
(t) in the form:
D
,
a
h
p
(t) =
1
(
1
)
t
d
dt
_
_
_
t
_
a
1

1
_
ln
t

1
d
d
f()d
_
_
_
, (15)
where
1
= (m), f() =
m1
I

a
h
p
(). Further,
I

a
h
p
() =
1
()

_
a
_
ln

_
1
h
p
()
d

=
448 B. Turmetov, K. Shinaliyev
=
1
()

_
a
_
ln

_
1

_
a
_
_

i=p

ip
(i + )
_
i
p
__
ln

z
_
i+1
_
_
h(z)
z
d

=
=

i=p

ip
(i + )
_
i
p
_
1
()

_
a
h(z)

_
z
_
ln

_
1
_
ln

z
_
i+1
d

dz
z
=
=

_
a
_
_

i=p

ip
(i + + )
_
i
p
_
_
ln

z
_
i+1+
_
_
h(z)
dz
z
Hence for a function f() we obtain
f() =
m
I

a
[h
p
]() =

_
a
_
_

i=p

ip
(i + + (m1))
_
ln

z
_
i++m
_
_
h(z)
dz
z
.
Consequently, integrating by parts in (15), we get
D
,
a
h
p
(t) =
1
(
1
)
t
d
dt
_
_
_
t
_
a
_
ln
t

1
1
f()
d

_
_
_
.
Further, as in the casep = 0 we have
t
_
a
_
ln
t

1
1
f()
d

= (
1
)
t
_
a
_
_

i=p

ip
(i + 1)
_
i
p
__
ln
t

_
i
_
_
h()

d.
It means that
D
,
a
h
p
(t) =
t
_
a
_
_

i=p

ip
(i)
_
i
p
__
ln
t

_
i1
_
_
h()

d =
=
t
_
a
_
_

j=p1

j(p1)
(j + )
_
j + 1
p
__
ln
t

_
j+1
_
_
h()

d.
Then
D
,
a
h
p
(t) h
p1
(t) =
=
t
_
a
_
_
_

i=p1
__
i + 1
p
_

_
i
p 1
__

i(p1)
(i + )
_
ln
t

_
i+1
_
_
_
h()

d =
ON A METHOD FOR CONSTRUCTING SOLUTIONS OF... 449
=
t
_
a
_
_
_

i=p
_
i
p
_

i(p1)
(i + )
_
ln
t

_
i+1
_
_
_
h()

d = h
p
(t).
Therefore,
D
,
a
h
p
(t) h
p1
(t) = h
p
(t),
i.e. for all p = 1, 2, ... the following equality holds:
_
D
,
a

_
h
p
(t) = h
p1
(t).
Theorem is proved. Theorems 1 and 2 imply the following basic statement:
Theorem 3. Let m 1 < m, , m = 1, 2,..., 0 1. Then the
function
y(t) =
m1

s=0
n1

p=0
C
s,p

p
,,s
(, t) +
t
_
a
_
ln
t

_
1
E
n1
,
_
,
_
ln
t

_
h()
d

is a solution of equation (1), where C


s,p
are constants.
Acknowledgments
This paper is nancial supported by the grant of MES RK No.0713/GF.
References
[1] A.A. Kilbas, H.M. Srivastava, J.J. Trujillo, Theory and Applications of
Fractional Dierential Equations, Elsevier, North-Holland (2006).
[2] M.D. Qassim, K.M. Furati, N.-E. Tatar, On a dierential equation involv-
ing hilfer-Hadamard fractional derivative, Abstract and Applied Analysis
(2012), Article ID 391062, 17.
[3] R. Hilfer, Y. Luchko, Z. Tomovski, Operational method the solution of
fractional dierential equations with generalized Rieman-Lioville fractional
derivatives, Fractional Calculus and Applied Analysis, 12, No. 3 (2009),
299-318.
[4] B.A. Bondarenko, Operator Algorithms in Dierential Equations,
Tashkent, FAN (1984), In Russian.
450 B. Turmetov, K. Shinaliyev
[5] K.M. Shinaliyev, B.Kh. Turmetov, S.A. Umarov, Fractional operator algo-
rithm method for construction of solutions of fractional order dierential
equations, Fractional Calculus and Applied Analysis, 15, No. 2 (2012),
267-281.
[6] B.Kh. Turmetov, K.M. Shinaliyev, On an operator method of construction
the solution of dierential equations of the fractional order, Vestnik of L.
Gumilyev Eurasian National University. Series for Natural and Engineer-
ing Sciences, 81, No. 2 (2011), 10-17.